Integrating sensory evaluation into biofortification breeding: assessing consumer acceptance and market segmentation of porridge made from biofortified pearl millet cultivars - Hamid, Manhal Gobara; Elsafy, Mohammed; Abdelhalim, Tilal (Frontiers in Nutrition, 2025)
IntroductionSensory evaluation is a crucial tool in biofortified pearl millet breeding, influencing consumer acceptance and market expansion. This study aimed to evaluate the sensory attributes and consumer acceptability of stiff porridge (Aceda) prepared from biofortified pearl millet and its blends with traditional Sudanese cultivars to inform breeding and market strategies.MethodsThis study was conducted in 2023 at the Gadarif Research Station, Agricultural Research Corporation (ARC), Sudan. It evaluated the sensory attributes of stiff porridge (Aceda) made from biofortified pearl millet (Aziz), two widely adopted Sudanese cultivars (Ashana and Bayoda), and their blended formulations. To analyze consumer segmentation and preference patterns, 28 semi-trained assessors conducted hedonic scoring and rapid descriptive profiling. The data were analyzed using internal preference mapping (IPM), panel analysis, product characterization, and partial least squares regression (PLSR) using XLSTAT.Results and discussionThe results revealed significant variation among the five Aceda products (analysis of variance (ANOVA), F = 11.84, p < 0.001), with the Bayoda + Aziz blend receiving the highest liking score (mean = 7.7) and Aziz alone the lowest (mean = 5.8). Principal component analysis (PCA) explained 71.47% of total variation in consumer preference, while PLSR identified taste, firmness, aroma, and texture as key drivers of acceptance. Panel analysis revealed that firmness (F = 13.22, p < 0.0001), color, and appearance exhibited the highest discriminative power among the descriptors. Short-term recommendations include blending biofortified cultivars with preferred local varieties to enhance adoption. Long-term strategies should integrate omics-enabled breeding with sensory and market-oriented selection.ConclusionThis study provides the first quantitative evidence of consumer sensory preferences for biofortified Aceda, emphasizing that blending strategies significantly enhance acceptability. Integrating sensory evaluation into early stage breeding, alongside artificial intelligence (AI) and rapid sensory tools, will accelerate the adoption of biofortification and support nutrition-sensitive breeding.